Finite element analysis of traditional and new fixation techniques of the 3d-printed composite interlocking nail in canine femoral shaft fractures - Siwasit Pitjamit (2020)
© 2020 by the authors. Since the removal of a metallic interlocking nail system leaves a blank cavity inside a healed bone, bioactive and biodegradation materials have been used instead to induce bone formation and eliminate complications of the material removal procedure. The previous study presented the possibility of an interlocking nail fabrication from polylactic acid (PLA), polycaprolactone (PCL), and hydroxyapatite (HA) using 3D printing, namely fused filament fabrication (FFF), for canine diaphyseal fractures. Therefore, a finite element analysis (FEA) was used to predict the maximum principal stress of this 3D-printed composite interlocking nail to stabilize a canine femoral fracture, and the biomechanical performance was evaluated for the treatment of canine femoral shaft fractures using both traditional and new fixation techniques. Three-dimensional FEA models were created, and the composite interlocking nail was tested for implant strength and stability. Three types of canine femoral shaft fracture (proximal shaft fracture, middle shaft fracture, and distal shaft fracture) fixed by traditional and new fixation techniques, consisting of two, four, and six locking screws, were analyzed with a multilevel factorial design technique. The maximum principal stresses of the composite interlocking nail were compared with each fixation technique. According to the multilevel factorial design, gap type, fracture gap, and fixation techniques are factors that affect the maximum principal stress of the composite interlocking nail for two and four locking screws. For six locking screws, all factors, including gap type, fracture gap, nail length, and fixation techniques, significantly affect the maximum principal stress. The use of a 3D-printed composite interlocking nail system with new fixation techniques demonstrated lower maximum principal stresses than the interlocking nail system that used a traditional fixation technique. The results of this study could help orthopedic veterinary surgeons to understand the biomechanical performances of traditional and new fixation techniques. Furthermore, surgeons may use the numerical results of this analysis to choose a fixation technique based on a patient's condition.